The use of lexical bundles by English majors in IIUM - Siti Aidayati binti Che Ya (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
'Lexical bundle' is seen as one aspect of phraseology that depends on frequency and cut-off points. Often overlooked, lexical bundles and the subject of this study investigates the production of these items by IIUM's English majors in two different cohorts – Lower Level (first and second years) and Upper Level (third and fourth years) using corpus-derived data on frequency, structural and functional categories. A small corpus of student essays comprising 114,968 words was created for this investigation. Drawing on a phraseological view of language (Granger & Meunier 2008), the study used AntConc 3.2.1 to retrieve recurrent word combinations in the essays written by the students. The study revealed that the two groups, despite being in different stages of study, employed almost similar recurrent word combinations in their writing. While the high level of similarity could be attributed to the topics being discussed and the prompts that formed the essay questions, further investigation of the groups' rankings of the lexical bundles suggests that the essays were also similar in their rhetorical style and grammar deployment. The analyses on structural and functional features suggest the students were capable of producing meaningful and functional lexical bundles though the huge similarities may also point to the students' lack of creativity and limited exposure to other choices of lexical bundles.